A study of the life and works of Athanasius Kircher, "Germanus incredibilis" : with a selection of his unpublished correspondence and an annotated translation of his autobiography - Fletcher, John Edward. (Aries Book Series, 2011)
Athanasius Kircher, a German Jesuit in 17th-century Rome, was an enigma. Intensely pious and a prolific author, he was also a polymath fascinated with everything from Egyptian hieroglyphs to the tiny creatures in his microscope. His correspondence with popes, princes and priests was a window into the restless energy of the period. It showed first-hand the seventeenth-century's struggle for knowledge in astronomy, microscopy, geology, chemistry, musicology, Egyptology, horology... The list goes on. Kircher's books reflect the mind-set of 17th-century scholars - endless curiosity and a substantial larding of naiveté: Kircher scorned alchemy as the wishful thinking of charlatans, yet believed in dragons. His life and correspondence provide a key to the transition from the Middle Ages to a new scientific age. This book, though unpublished, has been long quoted and referred to. Awaited by scholars and specialists of Kircher, it is finally available with this edition.